An Analysis and Survey of Polishing Dents Warehouse Inventory Development - S Pasaribu, Johni (Malikussaleh University, Aceh, Indonesia, 2022)
PT Setia Kiji Reed (SKR) was established in 1991, with its Jl address. Rancaekek Km. 24.5, Linggar, Kec. Rancaekek, Bandung Regency, West Java 40394 is a company that already uses computer technology in carrying out its business processes. This company is a joint venture between Japan (KIJI Reed Co. Ltd) and Indonesia, with business activities in the textile industry such as manufacturing and sales of reeds for weaving looms and material suppliers for air-jet reeds. The company has three divisions: Wirecut, Polishing Dents, and Reed Production. However, recording incoming and outgoing goods transactions at the Polishing Dents warehouse is not fully recorded in one application but is stored in various databases. Each punch-out or raw material from the supplier is stored in the warehouse as a raw material., These goods are processed through the production process into finished goods, held in the warehouse as finished goods for export. The data obtained in this study were collected by interview, observation, and literature study. Software development uses the Rapid Application Development (RAD) methodology and a system design approach through the Object-Oriented Approach with the Unified Modeling Language (UML). The results of this study are an inventory management information system that can support and manage inventory processes in the warehouse, such as controlling and monitoring goods, maintaining goods returns, assigning suppliers, and reporting.